A thermodynamic description of the U−Ti−Zr system. (March 2018) - Zeng, Yinping; Zhou, Peng; Du, Yong; Mo, Wenlin; Bai, Bin; Wang, Xiaolin; Zhao, Jingrui
Abstract: The U−Ti−Zr system was assessed by means of the CALPHAD method for the first time. Based on a critical evaluation of experimental phase diagram data available in the literature, a thermodynamic modeling was conducted for the individual phases. The solution phases including the liquid, hcp and bcc were described by a substitutional solution model. The binary compounds, U2 Ti and UZr2, with a ternary extension were treated as one single phase using a sublattice model of (U, Zr)2/3 (Ti, Zr)1/3 . There is no ternary compound in this system. A set of self-consistent thermodynamic parameters for the U−Ti−Zr system was then obtained. Comparisons between the calculated and measured phase diagrams show that the experimental information is satisfactorily accounted for by the present thermodynamic description. The solvus projection and reaction scheme were generated using the present thermodynamic parameters. The presently calculated phase diagrams of U–Zr−Ti alloys can be used for further industrial application.